In Face on Facebook: Brooklyn's Drag Community and Sociotechnical Practices of Online Communication. Issue 5 (1st June 2015) - Lingel, Jessa; Golub, Adam
Abstract: Recently, Brooklyn has seen an explosion of drag culture, with dozens of performers taking the stage in any given week. Social media plays a vital role for members of this community, simultaneously allowing self-promotion and community solidarity. Drawing on focus group interviews, we analyze the communication practices of Brooklyn's drag performers, examining both the advantages and drawbacks of social media platforms. Using conceptual frameworks of faceted identity and relational labor, our discussion focuses on affordances and constraints of multifaceted identity in online contexts and theories of seamful design. We contend that by analyzing online communication practices of drag performers, it becomes possible to identify gaps between embedded ideologies of mainstream social media technologies and the localized values of outsider communities.